Core–shell hierarchical WO2/WO3 microspheres as an electrocatalyst support for methanol electrooxidation. Issue 83 (4th September 2015) - Zhou, Yang; Hu, Xian-Chao; Liu, Xi-Hui; Wen, He-Rui
Abstract : Core–shell WO2 /WO3 microspheres were used to prepare a Pt–WO2 /WO3 catalyst with a mass specific current of 694 mA mg −1 which is 1.4 and 3.0 times greater than those of commercial PtRu/C and Pt/WO3 . Abstract : Core–shell WO2 /WO3 microspheres were prepared using a phase transformation route. The as-prepared Pt–WO2 /WO3 catalyst exhibits excellent activity and stability towards methanol electrooxidation, compared with those of commercial PtRu/C and Pt/h-WO3, due to the decrease of the electron-transfer resistance by the modification of using WO2 as a conductive oxide.